The role of Abdullah Qadiri in Uzbek novels - Melikuziyev Mumtozbek Zarifjon o’g’li (Zien Journals, 2021)
This article deals with the life and work of Abdullah Qadiri, his thoughts on the Jadid movement, and the novels he wrote as the founder of Uzbek romance
Keywords: Uzbek novel; Mushtum; Young married woman; romance